Strategy for Winning Women's Legislature in the 2019 Malang General Election - Atika Candra Larasati; Darsono Darsono; Sanggar Kanto; Yayuk Yuliati (Publikasi Indonesia, 2022)
This study aims to explore strategies for winning women's legislatures in politics. Women in the history of civilization are often number two. With the help of previous studies, we can find out that the impacts that women bring on politics to policy making have a significant positive impact. This study uses a qualitative research method with a phenomenological approach. The location in this study is Malang Raya (Malang City, Batu City and Malang Regency) as the second largest city and an education city located in East Java province, where East Java province is known as a province with mature political maturity in Indonesia because several stakeholders important power is women. With the help of some descriptive data that shows the level of participation or representation of women in government in Malang Raya, the researchers focused on how the strategies of these women in enabling themselves to assume power. The results of the study show that various strategies used by women in Malang Raya in winning legislative seats can be used as further studies as points that allow for an increase in the realization of women's representation in government.